Comprehensive identification, characterization, and expression analysis of m6A methylation transferase gene family in maize (Zea mays L.) - Li, Chunlei; He, Ming; Liu, Xinyi; Lv, Qingxue; Yu, Xiaoming; Fan, Xiaoxue; Bai, Xia; Cong, Jie; Sun, Chuanbo (Frontiers in Plant Science, 2025)
N6-methyladenosine (m6A) RNA represents the most prevalent internal modification found in mRNA and plays a crucial role in stress response and developmental processes across various crop species. However, the understanding of m6A modification in monocot species remains limited. In this study, we conducted a comprehensive analysis of m6A methyltransferase genes “writers” in maize, focusing on gene localization, structural characteristics, conserved domains, phylogenetic relationships, promoter analysis, and expression profiles. Our analysis identified three m6A regulatory genes within the maize genome. Through the phylogenetic relationship analysis, we classified these genes into three distinct clusters alongside the model species Arabidopsis thaliana and Oryza sativa. Promoter analysis revealed that m6A pathway genes are mainly associated with hormone-responsive elements, environmental stress-related elements, and transcription factors. The conserved domain analysis indicated that all identified maize m6A proteins possess the MT-A70 domain. Furthermore, RNA-seq and RT-qPCR analysis demonstrated that the identified Zmm6A genes exhibit tissue-specific expression patterns, as well as differential expression in response to various abiotic stresses, suggesting a potential role for m6A modification in influencing reproductive development. Notably, the expression of ZmMTA-03 genes was significantly upregulated under cold stress conditions. This study provides valuable insights into the regulatory genes associated with m6A modification and their potential epigenetic regulatory mechanisms in maize.